(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The article analyzes the results of the determination of the salinity level and the creation of cartograms of irrigated agricultural land in the Bostan district of Andijan region, which is part of the Central Fergana region, carried out in 2017. When determining the salinity level, the secondary salinity level of the soils was determined, taking into account the relief location of the research object and the chemistry of salinity, and recommendations were given on the rate, duration, and number of salt leaching operations.